International Commodity Taxation Under Monopolistic Competition - Andreas Haufler; Michael Pflüger (Center for Economic Studies and ifo Institute (CESifo), 2001)
We analyze non-cooperative commodity taxation in a symmetrictwo-country trade model characterized by monopolisticcompetition and international firm and capital mobility. In thissetting, taxes in one country affect foreign welfare through therelocation of mobile firms and through changes in the rentsaccruing to capital owners. With consumption-based taxation,these fiscal externalities exactly offset each other and the non-cooperativetax equilibrium is Pareto efficient. With production-basedtaxation, however, there is an additional externality on theforeign price level which leads non-cooperative tax rates toexceed their Pareto efficient levels.
Keywords: 330; tax competition; market imperfections; internationaltrade